The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1002/imhj.21911
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study on the course of sleep disturbances in first‐time fathers during the transition to parenthood

Abstract: Introduction: This study examined sleep disturbances in first-time fathers from the third trimester of their partner's pregnancy to 2 months postpartum to determine prevalence, incidence, and persistence of sleep disturbances and identify associated determinants. Methods: Men expecting their first child were recruited from local prenatal classes and university-affiliated obstetric clinics. During their partner's third trimester of pregnancy and 2 months postpartum, 459 men completed standardized online self-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 84 publications
0
4
0
Order By: Relevance
“…Given the importance of relationship quality perceptions for both relational outcomes and general well-being (e.g., Finkel et al, 2017), understanding the influences of relationship quality and targeting intervention strategies addressing these is crucial. There are periods in a relationship where detriments to sleep quality are more likely, such as during the transition into parenthood (Da Costa et al, 2021), retirement (Alhainen et al, 2020), menopause (Polo-Kantola, 2007), or periods of increased stress (Sun Han et al, 2012). During these times when poor sleep is often unavoidable, targeting marital interventions to address anger awareness and emotional regulation may be useful (e.g., Finkel et al, 2013; Gross & Jazaieri, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Given the importance of relationship quality perceptions for both relational outcomes and general well-being (e.g., Finkel et al, 2017), understanding the influences of relationship quality and targeting intervention strategies addressing these is crucial. There are periods in a relationship where detriments to sleep quality are more likely, such as during the transition into parenthood (Da Costa et al, 2021), retirement (Alhainen et al, 2020), menopause (Polo-Kantola, 2007), or periods of increased stress (Sun Han et al, 2012). During these times when poor sleep is often unavoidable, targeting marital interventions to address anger awareness and emotional regulation may be useful (e.g., Finkel et al, 2013; Gross & Jazaieri, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Sleep affects physical and mental health outcomes [ 1 , 2 ]. Restorative sleep is important for physical, cognitive, and psychological well-being [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…New parents experience frequent sleep disruptions due to nighttime care for their infant. Sleep changes across the first postpartum year can have a negative impact on mood, relationships, and quality of life (Da Costa et al, 2021; Medina et al, 2009; Simard et al, 2021). Studies of parents of infants and toddlers have also identified that the quality of the child’s sleep predicts parent’s sleep quality (Meltzer & Mindell, 2007; Sinai & Tikotzky, 2012).…”
Section: Introductionmentioning
confidence: 99%